2010
DOI: 10.1038/onc.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

The SFRP family of WNT inhibitors function as novel tumor suppressor genes epigenetically silenced in medulloblastoma

Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor. Dysregulation of WNT signaling occurs in up to 20% of cases. Using a genome-wide approach, we identified the secreted frizzled-related protein 1, 2 and 3 (SFRP1, SFRP2 and SFRP3) family of WNT inhibitors as putative tumor suppressor genes silenced by promoter region methylation in MB. SFRP1, SFRP2 and SFRP3 expression increased after 5-aza-2 0 -deoxycytidine treatment. SFRP1, SFRP2 and SFRP3 methylation was identified in 23.5, 3.9 and 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 21 publications
4
67
0
1
Order By: Relevance
“…Alternatively, activation of MMPs after sFRP2 blockade or MSC therapy may release VEGF and HGF from the ECM niche as demonstrated for basic fibroblast growth factor by Whitelock et al (63). This VEGF-antagonizing effect of sFRP2 appears in line with the emerging notion that sFRP2 may represent a novel tumor-suppressor gene, the expression of which is often silenced in cancer cells (29). Saline Control sFRP2 antibody A B Fig.…”
Section: C535supporting
confidence: 51%
“…Alternatively, activation of MMPs after sFRP2 blockade or MSC therapy may release VEGF and HGF from the ECM niche as demonstrated for basic fibroblast growth factor by Whitelock et al (63). This VEGF-antagonizing effect of sFRP2 appears in line with the emerging notion that sFRP2 may represent a novel tumor-suppressor gene, the expression of which is often silenced in cancer cells (29). Saline Control sFRP2 antibody A B Fig.…”
Section: C535supporting
confidence: 51%
“…109 Germline mutations in the adenomatous polyposis coli (APC) gene cause Turcot syndrome and more rarely sporadic medulloblastoma. 58 Using an epigenetic genome-wide approach, Kongkham et al 72 identified a group of Wnt inhibitors-the secreted frizzled-related protein family (SFRP1, SFRP2, and SFRP3)-that function as tumor suppressor genes and are silenced by promotor methylation in medulloblastoma. Secreted frizzled-related protein expression reduced cell proliferation and anchorage-independent growth in vitro and impaired tumor formation in vivo.…”
Section: 143mentioning
confidence: 99%
“…The SHH pathway was inhibited in pancreatic cancer and MDS cell lines, resulting in decreased DNMT1 expression, whereas induction of the SHH pathway resulted in higher DNMT1 expression [16,40]. In contrast, DNMT1 inhibition resulted in increased expression of SFRP1 in MB cell lines [20]. One explanation could be that investigated MB cell lines do not belong to the SHH subgroup, since they showed lower levels of SFRP1 compared to the SHH subgroup.…”
Section: Discussionmentioning
confidence: 65%